Assessing flash flood occurrences and hazard zones along the mediterranean coasts: a GIS and mapping techniques approach in the Wadi Saf Saf Basin, Northeast Algeria - Maou, Amal; Souadnia, Sabrina; Faqeih, Khadeijah; AlAmri, Afaf; Hadji, Riheb; Alamri, Somayah moshrif; Harizi, Khaled; Alamery, Eman; Sonia, Griche; Leila, Boubazine; Altwaiher, Jamilah (Frontiers in Earth Science, 2025)
Flash floods represent one of the most destructive forms of natural hazards, frequently resulting in severe property damage and loss of life. Their occurrence has intensified in recent decades, largely driven by climate change, unregulated urban expansion, and increased development in flood-susceptible downstream areas. The Wadi Saf Saf basin, located in northeastern Algeria, is particularly prone to such events. Flash flood hazard is investigated based on statistical morphometric analysis. This study explores the influence of morphometric characteristics on flash flood susceptibility within the basin. The implementation of GIS allows the automated extraction of morphometric parameters from digital elevation models (DEMs) for quantitative analyses, updating, and morphometric study of drainage basins. 22 key morphometric parameters; including stream order, drainage density, bifurcation ratio, elongation ratio, slope, and relief; were derived from remote sensing data and processed through empirical equations tailored to each parameter. The sub-watersheds were evaluated using an index-based scoring system to reflect their relative contribution to flood risk, and the linear overlay technique was employed to produce a comprehensive flash flood hazard (FFH) map. The resulting classification delineates five flood risk categories, from very low (e.g., sub-watershed 10) to very high (e.g., sub-watersheds 1, 2, 16, and 19). This integrated approach highlights the spatial variability of flood vulnerability across the Saf Saf watershed and offers essential support for disaster risk reduction, structural mitigation planning, and informed land-use management in Mediterranean catchments.